peningkatan penyakit jantung STUDI FENOMENOLOGI : PENINGKATAN KEBUTUHAN PELAYANAN GAWAT DARURAT PREHOSPITAL DI MASYARAKAT KALIMANTAN TIMUR - Misbah Nurjannah Nurjannah; Zulmah Astuti; Dwi Widyastuti (Poltekkes Kemenkes Kalimantan Timur, 2018)
Heart disease is leading causes of death in Indonesia. Heart disease has increased almost every year. Increased heart disease incidence was also matched by an increase in demand for emergency services related to cardiovascular disease in prehospital. The research method is done by qualitative interpretive involving 6 nurses who have emergency experience and competence in the emergency department. Data were obtained from in-depth interviews and analyzed using Braun and Clarke techniques. The results of the emergency nurses' research felt that the services provided were not maximal in prehospital. Emergency nurses should review cases to determine the priority that emergency services should be provided outside the Hospital. Emergency nurses provide emergency services mostly in conditions of heart disease. The experience of emergency nurses in providing emergency services is strongly influenced by their competence and experience in prehospital. Increasing the number of emergency nurses and the competence of nurses is important to improve the quality of emergency service in prehospital.